Etiological Spectrum and Risk Factors of Heart Failure Among Patients Admitted in Bharatpur Hospital - Gautam, Mani Prasad; Bhattarai, Surakshya; Shrestha, Bishal; Yadav, Rabindra; Panjiyar, Rajesh; Bista, Anupam (Journal of National Heart and Lung Society Nepal, 2025)
Background: Heart failure (HF) is a major public health concern globally and increasingly prevalent in low and middle-income countries like Nepal. Understanding its etiological spectrum and associated risk factors is essential for formulating effective prevention and management strategies. Methods: A cross-sectional descriptive study was conducted among 210 adult patients admitted with heart failure to Bharatpur Hospital from January to December 2023. Data on demographics, clinical features, risk factors, and etiologies were collected through structured questionnaires and clinical evaluations, including echocardiography. Statistical analysis was performed using SPSS version 20. Results: The mean age of patients was 62.4 ± 12.7 years, with a male predominance (65.7%). The leading risk factors identified were hypertension (65.7%), diabetes mellitus (48.6%), physical inactivity (48.6%), and dyslipidemia (40%). Dyspnea on exertion (94.3%) was the most common presenting symptom. Ischemic heart disease emerged as the predominant etiology (48.6%), followed by hypertensive cardiomyopathy (25.7%) and valvular heart disease (17.1%). Conclusion: Ischemic and hypertensive heart diseases are the primary causes of HF among hospitalized patients in Bharatpur, with a high prevalence of modifiable risk factors. These findings highlight the urgent need for community based prevention strategies and integrated cardiovascular risk management at the primary care level.